Detection of Ocean Tide Loading Constituents Based on Precise Point Positioning by GPS - Jihye Won; Kwan-Dong Park (Journal of Astronomy and Space Sciences, 2009)
In this study, the Ocean Tide Loading (OTL) constituents were detected by the Precise Point Positioning (PPP) technique using GPS. Then, the GPS estimates of OTL constituents were compared with the predictions of the ocean tide models. We picked three permanent GPS stations as test sites and they are ICNW, SEOS, and CJUN. To detect the OTL constituents using GPS, we created vertical coordinate time series at 10-minute intervals using the PPP approach implemented in the GIPSY software. Through the tidal harmonic analysis of this height time series, the four major constituents (M2, S2, K1, O1) were determined. The amplitude obtained from the GPS height time series of the OTL constituents showed best match with the model predictions at CJUN, while the phase showed closest match at ICNW. The amplitude accuracy of the M2, which is the dominant factor out of the 11 major constituents, was 24.8% on average.